KUALITAS PENGUNGKAPAN SDGs DAN GREEN ACCOUNTING: IMPLIKASI KINERJA KEUANGAN - Meiliana, Reva; Angga Wijaya, M. Reza; Siregar, Nolita Yeni (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to obtain empirical evidence the effect of the Quality of SDGs Disclosure and Green Accounting on the company”s Financial Performance. The population in this study is sector energy companies listed on the Indonesian Stock Exchange (IDX) During for the period 2020 – 2022. This study uses purposive sampling method with several criteria which are then sampled. The analysis method used is quantitative analysis with secondary dta taken from annual reports and sustainability reports, which includes 60 sample of energy sector companies listed on the IDX. The tests carried out using multiple linear regression models, and data analysis tools were carried out with the SPSS version 25 program. The result of this study showed that the Quality of SDGs Disclosure variable has effected on Financial Performancce, and Green Accounting variable has no effect on Financial Perfomance. Keywords: SDGs, Green Accounting, ROA